Description of Predisposing, Enabling and Reinforcing Factor on Society in the Utilization of Sanitation Clinic in Kelurahan Baru Ladang Bambu Kecamatan Medan Tuntungan Kota Medan in 2014. - Widya Oktalisa; nurmaini *; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Sanitation Clinic is the public place for overcome the environmental health problem and disease based on environment with guidance, counseling, and technical help from public health centre workers. It is not as an independent service unit, but as an integral part of the health centre activities, cooperated by interprogram and intersectoral that is in the working area of public health centre. This research aim to know the description of predisposing, enabling and reinforcing factor on society in utilization of sanitation clinic at Kelurahan Baru Ladang Bambu Kecamatan Medan Tuntungan Kota Medan. The kind of this research is descriptive using of the cross sectional design. The population is the society of Kelurahan Baru Ladang Bambu which amounts to 858 patriarch. Starting at of taking sample according to systematic random sampling, obtained sample as much as 90 patriarch. Result of this research has been shown that predisposing have good knowledge of 52.2 percent, good attitude of 44.4 percent, good credibility of 86.7 percent. Enabling factor has been shown that if the presence of facilities and infrastructure of sanitation clinic were good of 13,3 percent, and the whole socialization of it was not good. Reinforcing factor has been shown that if the presence of sanitation clinic workers were good of 25.6 percent. Suggested in implementation of it, in order that increased the socialization by sanitation clinic workers and they should be active to society, and the instance beside of this program could do the monitoring for doing the revitalitation, and for the goverment could giving more budget for the sake of the continuity of  facilities and infrastructure. Key words : Predisposing, Enabling and Reinforing Factor, Sanitation Clinic.